Teaching competencies and entrepreneurial performance among the Hashemite University faculty members - Issa, Hytham M. Bany; Al-Zoubi, Zohair H.; Bataineh, Omar T.; Bani-Issa, Hassan Mohammad; Altarawneh, Awad Faek (Institute of Advanced Engineering and Science, 2025)
The study examines the application of teaching competencies among faculty members at Hashemite University and investigates their relationship with perceived entrepreneurial performance within a quality assurance framework. Using a descriptive-relational survey design, a sample of 340 faculty members was selected through stratified sampling during the first semester of the 2022/2023 academic year. Data were collected via a validated questionnaire measuring teaching competencies across five domains—personal, academic, administrative, cultural, and professional—and entrepreneurial performance. The findings indicated that both teaching competencies and entrepreneurial performance were at a moderate level. A positive and statistically significant relationship was identified across all competency dimensions and entrepreneurial performance, suggesting that enhanced competencies can positively impact entrepreneurial outcomes. Based on these results, the study recommends integrating teaching competency evaluations into university quality assurance policies and suggests combining intrinsic and extrinsic incentives to foster faculty productivity. These recommendations offer valuable insights for enhancing academic standards and fostering entrepreneurial skills among faculty in higher education.